Study on snow collection regularity and movement characteristics of snow particles in double-spiral ribbon - Chu-Qi Su; Qian Lei; Xun Liu; Yi-Ping Wang; Xu-Jun Li (Case Studies in Thermal Engineering)
To improve the snow removal efficiency of the snow blower on the road in winter, a three-dimensional numerical simulation method of the snow collector of the double-spiral ribbon is proposed, the air-snow two-phase flow in the rotating region of the double-spiral ribbon of a snow blower is numerically simulated based on the Euler particle phase method.The simulation model is verified according to the test results,and the snow collecting performance of the double-spiral ribbon on the snow entering the rack area and the motion characteristics of snow particles are studied under different rotation speed and snow collecting height. The results show that when the speed of the ribbon increases from 20 rpm to 200 rpm, the speed of snow particles at the exit increased by 63.3 %. but the ribbon's snow collection efficiency is reduced by 20 %. When the snow height increases from 0.1m to 0.6m, The average speed of snow particles flowing out of the rack area after the acceleration of the ribbon increased by 11 %. When the snow height exceeds 0.3m, snow collection efficiency declines sharply. Overall, this paper provides the most reliable and useful snow collecting regularity and snow particle movement rules for the design and production of the Snow Blower.